Metabolic Surgery Enters the T2DM Treatment Algorithm. (October 2016) - Moncada, Rafael; Landecho, Manuel F.; Frühbeck, Gema
Abstract : A Joint Statement endorsed by 45 international organizations, clinicians, and researchers indicating when to recommend or consider metabolic surgery in type 2 diabetes mellitus (T2DM) treatment has been recently published. These new guidelines, resulting from the Second Diabetes Surgery Summit (DSS-II), represent the most radical change in T2DM management of the past few decades.